A Precarious Child Becomes a STEAM Learner: Journey of Discrimination, Struggle, and Envisioning - Reshmi, Dhan Bahadur (Chhahari छहारी, 2026)
This paper narrates the academic journey of the author from a precarious child to a STEAM learner, crossing up and down moments across the time period. The purpose of this study is to explore how an indigenous child endured the discriminatory burdens as a hegemonic practice of the education system of Nepal. The paper is framed in an autoethnographic research design explaining lived experiences, feelings, and events as the discriminatory burdens, learning struggles, and envision for a better future of school science education. The paper discussed four major themes: research discrimination, research struggles, and envisioning justice-oriented STEAM education. An untouchable school environment and discriminatory responses from the teachers are the major concerns of this paper. Based on the discussion conclusion is drawn that the culturally responsive approaches can address the raised issues in the classroom, and open the floor for the development of local epistemologies.